Bacterial cell recovery after hollow fiber microfiltration sample concentration: Most probable bacterial composition in frozen vegetables. (April 2021) - Irwin, Peter; He, Yiping; Nguyen, Ly; Gehring, Matthew; Gehring, Andrew G.; Chen, Chin-Yi; Capobianco, Joseph
Abstract: A commercial "concentrating pipette" was scrutinized from the perspective of sample volume reduction to augment native bacterial quantitation and identification within food samples. Aspects related to the elution protocol were evaluated for their impact on bacteria recovery. The results demonstrated there was no significant effect from different diluents/eluents on the relative recovery rate. Further, results from a complementary technique, dynamic light scattering, imply that recoveries less than unity are likely due to an inability to completely elute the bacterial cells from the capillary filter as opposed to bacterial injury caused by sample processing. When concentrating PBS washes from thawed frozen vegetables and enumerating after culturing at either 30 or 37 °C, the recovery rates were only slightly lower than the simplified experimental conditions. However, in food wash samples, significantly more mass-normalized bacteria were recovered at the lower culture temperature. Nevertheless, the vegetable wash concentration process did not change the most probable isolate composition relative to that of the controls at either culture temperature. The study demonstrates the potential for the system to serve as an effective tool for bacterial recovery and concentration within water-based food systems such as equipment rinses, process wash water, and other samples coming from food processing plants. Highlights: Effective process for separating bacteria from food samples to improve detection. Bacteria captured on membranes are recovered using foam to reduce elution volume. Bacteria are concentrated without centrifugation, incubation or transfer steps.